Inhibition of major integrin αVβ3 reduces Staphylococcus aureus attachment to sheared human endothelial cells. (28th October 2016) - McDonnell, C. J.; Garciarena, C. D.; Watkin, R. L.; McHale, T. M.; McLoughlin, A.; Claes, J.; Verhamme, P.; Cummins, P. M.; Kerrigan, S. W.
Abstract : Essentials Staphylococcus aureus ( S. aureus ) binds and impairs function of vascular endothelial cells (EC). We investigated the molecular signals triggered by S. aureus adhesion to EC. Inhibition of the EC integrin αVβ3 reduces S. aureus binding and rescues EC function. αVβ3 blockade represents an attractive target to treat S. aureus bloodborne infections. Summary: Background: Vascular endothelial dysfunction with associated edema and organ failure is one of the hallmarks of sepsis. Although a large number of microorganisms can cause sepsis, Staphylococcus aureus ( S. aureus ) is one of the primary etiologic agents. Currently, there are no approved specific treatments for sepsis, and the initial management bundle is therefore focused on cardiorespiratory resuscitation and mitigation of the immediate threat of uncontrolled infection. The continuous emergence of antibiotic‐resistant strains of bacteria necessitates the development of new therapeutic approaches for this disease. Objective: To identify the molecular mechanisms leading to endothelial dysfunction as a result of S. aureus binding. Methods : Binding of wild type and Clumping factor A (ClfA) deficient S. aureus Newman to the endothelium was measured in vitro and in the mesenteric circulation of C57Bl/6 mice. The effects of the αV β3 blocker–cilengitide–on bacterial binding, endothelial VE‐cadherin expression, apoptosis, proliferation and permeability were assessed. Results: The major S. aureus cell wall protein ClfA bound to endothelial cell αV β3 in the presence of fibrinogen. This interaction resulted in disturbances in barrier function mediated by VE‐cadherin in endothelial cell monolayers, and ultimately cell death by apoptosis. With a low concentration of cilengitide, ClfA binding to αV β3 was significantly inhibited both in vitro and in vivo . Moreover, preventing S. aureus from attaching to αV β3 resulted in a significant reduction in endothelial dysfunction following infection. Conclusion: Inhibition of S. aureus ClfA binding to endothelial cell αV β3 by cilengitide prevents endothelial dysfunction.